Ophidian’s head, reptile’s eyes. On París-Austerlitz, by Rafael Chirbes - Valls, Fernando (Caracol, 2016)
The present paper discusses Rafael Chirbes’ last novel, Paris-Austerlitz. The novel tells about the encounter between a middle-aged French worker and a wealthy Spanish young man who wishes to be a painter, in a sordid and naturalist Paris during 1986. Their relationship, an appropriate territory for class struggle, moves through passion, interest, jealousy and lack of love, though the rising of the plague, the evil, is going to lead the more devoted and less pragmatic of them to death.